Modelagem da qualidade da água na bacia hidrográfica do Rio Piracicaba - MG - Mayte Maria Abreu Pires de Melo Silva (2014)
The quality of water resources is compromised due to indiscriminate use of water and continued to dump stocks of residential waste, industrial waste and agriculture. An efficient way to assess the impacts of the release of pollutant loads as well as to analyze scenarios of intervention and measures of environmental controls, is through the use of water quality models, which are able to simulate different scenarios of development in the basin, leading into account both point as diffuse sources of pollution, assisting in the planning and management of water resources in a watershed. In this context, the study aims to achieve the application and calibration of a hydrological model, the MGB - IPH in Piracicaba river basin - MG, for further use of the data flows in model quality. Simulated and observed flows showed good correlation, which allows you to sort the model's performance as satisfactory. The water quality model used was the SAD- IPH, modeling BOD, DO, total phosphorus , nitrogen and total coliforms. To this end, the model was calibrated and validated using data from stations monitoring water quality IGAM. The curves of BOD, DO and total phosphorus showed good adherence to data from monitoring campaigns. The organic nitrogen, ammonia, nitrite, nitrate and coliform parameters did not fit well presenting simulated concentration values different from those measured. The simulation of a scenario of development that considers the installation of effluent treatment systems at all sites where the release is conducted directly into the water course was held. The results indicate that there was significant reduction in the concentration of pollutants simulated, however, was not enough for all watercourses would fit in class 2 of CONAMA.